A case study for the IONEX CODE-database processing tool software: Ionospheric anomalies before the Mω 8.2 earthquake in Mexico on September 7, 2017 - Zarate Segura, Guillermo Wenceslao (2018)
A software tool was developed in the Imaging Processing Research laboratory (INTI-Lab) that automatically downloads several IONEX files around a specific user input date and also performs statistical calculations to look for ionospheric anomalies through the generation of differential vertical total electron content (ΔVTEC) maps. The IONEX CODE-Database Processing Tool (ICPT) software allows to save a considerable amount of time spended in gathering the necessary IONosphere map EXchange (IONEX) files for the production of differential VTEC maps. Using the ICPT software we were able to detect ionospheric anomalies before the devastating earthquake that happened in Mexico on September 7, 2017. A positive and negative ionospheric anomalies were detected nine days and one day before the seismic event. Due to stable geomagnetic conditions we suggest that the anomalies are assocciated to the earthquake event. Furthermore, It is very likely that the collision between the North American and Coco's plate is producing the ionization necessary of the air to generate the disturbances observed.